2013
DOI: 10.1681/asn.2012070663
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Impact of Humoral Immunity in Pediatric Renal Transplantation

Abstract: The development of anti-donor humoral responses after transplantation associates with higher risks for acute rejection and 1-year graft survival in adults, but the influence of humoral immunity on transplant outcomes in children is not well understood. Here, we studied the evolution of humoral immunity in lowrisk pediatric patients during the first 2 years after renal transplantation. Using data from 130 pediatric renal transplant patients randomized to steroid-free (SF) or steroid-based (SB) immunosuppression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 37 publications
8
55
2
Order By: Relevance
“…A similar association has now been shown in children, demonstrating that the detection of DSAs is associated with impaired graft survival [58]. Interestingly, Chaudhuri et al observed that non-HLA antibodies, such as MICA antibodies, were also associated with subsequent worsening graft function [59]. The underlying trial was a steroidavoidance study, and unexpectedly, the amount of DSAs detected was higher in the steroid group than in the group not receiving steroids.…”
Section: Chronic Antibody-mediated Rejection (Camr)mentioning
confidence: 66%
“…A similar association has now been shown in children, demonstrating that the detection of DSAs is associated with impaired graft survival [58]. Interestingly, Chaudhuri et al observed that non-HLA antibodies, such as MICA antibodies, were also associated with subsequent worsening graft function [59]. The underlying trial was a steroidavoidance study, and unexpectedly, the amount of DSAs detected was higher in the steroid group than in the group not receiving steroids.…”
Section: Chronic Antibody-mediated Rejection (Camr)mentioning
confidence: 66%
“…The difference observed between Fontana et al's (15) study and ours is probably because we used a more sensitive assay. Recently, Miyagawa-Hayashino et al (16) assessed the prevalence of DSAs among stable pediatric LT patients who had survived for >5 years: they found a prevalence of 48% at 11 years (min-max: [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] posttransplantation. This high prevalence of DSAs is probably related to the very long follow-up in this Japanese study (16).…”
Section: Discussionmentioning
confidence: 99%
“…67 Reemerging B cells appeared to be naive, immature, and more regulatory in children than in adults. 66 By 3 to 5 years after transplantation, new antibodies directed against HLA antigens developed in 25% of children, 68 as compared with only 10% of adults. 69 Identification of relatively noninvasive biomarkers of acute rejection that might replace transplant biopsy is important.…”
Section: Pedi Atr Ic Immunosuppr Ession -Lessons From Clinic a L Tr Imentioning
confidence: 99%